(3bHS GdCfhGQ hLGeY GdCSQGQs - (3CHh YHO Gddg GdOYhQjs ((3eMeO Hf eMeO GdHdjSGfi GdUaGbSi s)
(3ChdgG (B:s
(3GeG HYO aEf GdHQi SHMGfg GHOY GdehLhOGJ s
(3BNQgG (B:s
(3dGf cd eG jbY ajg GdNdGa de JWeFf GdfahS s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GeHQhRjGfG s
Keywords: (3GdMQha h GdChaGbs